PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP FIRM VALUE DIMODERASI OLEH GOOD CORPORATE GOVERNANCE (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014) - Jessica Fiona; Kirmizi Ritonga; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purposes of this study are to analyze the effect of corporate social responsibility (CSR) disclosure to firm value and find out if good corporate governance (GCG) moderates the relationship between CSR disclosures to firm value. The population in this study is manufacturing company listed in Indonesia Stock Exchange in 2012 - 2014. The sample is selected by purposive sampling method, and the number of samples obtained are 77 companies with three years of observation. This study uses SPSS 16 application to examine the variables of this study. The variables of this study are firm value as dependent variable, CSR disclosure as independent variable, and GCG as moderating variable. GCG in this study is measured with managerial ownership, institutional ownership, proportion of independent commissioners, size of board director, size of board commissioner and audit committee. The result show that the CSR disclosure significantly affects the firm value. Good corporate governance measured by managerial ownership and proportion of independent commissioners moderate the relationship between CSR disclosure to firm value, but good corporate governance measured by institutional ownership, size of board director, size of board commissioner and audit committee don’t moderate the relationship between CSR disclosure to firm value.Keywords: Corporate Social Responsibility Disclosure, Firm Value, Good Corporate Governance